Electrochemical Control of Calcium Carbonate Crystallization and Dissolution in Nanopipettes. Issue 12 (14th October 2016) - Perry, David; Parker, Alexander S.; Page, Ashley; Unwin, Patrick R.
Abstract: Electrochemically controlled nanopipettes are becoming increasingly versatile tools for a diverse range of sequencing, sizing, and imaging applications. Herein, the use of nanopipettes to induce and quantitatively monitor crystallization and dissolution in real time is considered, using CaCO3 in aqueous solution as an exemplar system. The bias between a quasi‐reference counter electrode in a nanopipette and one in a bulk solution is used to mix (or de‐mix) two different solutions by ion migration and drive either growth or dissolution, depending on the polarity. Furthermore, Raman spectroscopy can be applied simultaneously to identify polymorphs formed in the nanopipette. The technique is supported with a robust finite element method model that allows the extraction of time‐dependent saturation levels and mixing characteristics at the nanoscale. The technique shows great promise as a tool for rapidly screening growth additives and inhibitors, allowing eight different additives to be ranked in order of efficacy for crystal growth rate inhibition. Abstract : Mix it up and start again : A novel electrochemical method to study growth and dissolution kinetics at the nanoscale, as well as to quickly screen additives.